Response of bean cultivated in nutrient solution to levels of calcium and magnesium in the presence of aluminium - Souza, José Olimpio de; Nascimento, Clístenes Williams Araújo do; Martinez, Hermínia Emília Prieto (Pesquisa Agropecuaria Brasileira, 1998)
An experiment was carried out under greenhouse conditions utilizing the Milionário Mulatinho cultivar, to evaluate the effects of Ca and Mg levels, in nutrient solution containing Al, on the dry matter and content of nutrients in shoot and roots of bean (Phaseolus vulgaris L.). The experimental design consisted of an incomplete factorial with four levels of Mg and five levels of Ca, in the presence of 3.0 mg/L Al, and of a control (without Al), being as a whole ten treatments with three replications. Each vase had 4.8 L of ½ - power Clark solution, pH 4.5, and two plants of bean. The presence of Al reduced the production of dry matter of shoot and the uptake of Ca, Mg and P. On the other hand, the accumulation of P and Al in the roots was increased and the accumulation of K and dry matter in that part of the plant was unaffected by Al. The supplying of Ca in the nutrient solution increased the production of dry matter in the roots and, in a general way, it also increased the concentration and accumulation of nutrients in the plants. The increase of Mg in nutrient solution increased its accumulation by plant and the production of dry matter in shoot. The concentrations of Ca and Mg in solution positively interacted with P concentration and with the accumulation of P and Al in the root system.